2014
DOI: 10.1245/s10434-014-3653-2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Risk Assessment for Gastrectomy by Surgical Apgar Score

Abstract: The oSAS was not found to be a predictive factor for severe complications following gastrectomy in Japanese patients. A slightly modified SAS (i.e. the mSAS) is considered to be a useful predictor for the development of severe complications in elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 27 publications
3
54
1
1
Order By: Relevance
“…These findings are consistent with previous SAS validation studies in large patient populations, 9,10 other procedures, [11][12][13][14][15][16] and other surgical specialties. [17][18][19] The eSAS was a strong predictor of postoperative complications when treated as a dichotomized, categoric, or continuous variable.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These findings are consistent with previous SAS validation studies in large patient populations, 9,10 other procedures, [11][12][13][14][15][16] and other surgical specialties. [17][18][19] The eSAS was a strong predictor of postoperative complications when treated as a dichotomized, categoric, or continuous variable.…”
Section: Discussionsupporting
confidence: 92%
“…These variables were incorporated into a 10-point scoring system, referred to as the Surgical Apgar Score (SAS). The SAS has now been externally validated in a number of large patient populations, 9,10 for specific procedures, [11][12][13][14][15][16] and for surgical specialties. [17][18][19] These studies have demonstrated significant predictive value of the SAS for postoperative morbidity and mortality.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…The present study found that postoperative morbidity significantly differed in the elderly, patients with more comorbidities, and those patients who underwent longer operation time. All of these factors had been reported in the previous studies, but the findings were not the same in those studies [27][28][29][30]. This difference may be due to the difference in the definitions of postoperative complications used, the different extents of lymphadenectomy, and the differences in surgeons' experience with the laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 81%
“…In 2011, Lee et al [27] first used the Clavien-Dindo system to evaluate the postoperative complications in LDG and open distal gastrectomy. Recently, the incidences of morbidity rates for laparoscopic surgery vary from 11.0 to 25.3 % [27][28][29][30], and the complication rates for LTG are reported to be higher than those for LDG because of technical difficulties. However, in this study, the postoperative morbidity rate in LTG group was 15.1 % and the mortality rate was 0.4 %, which were slightly higher than that in the LDG group, but without statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%